Identification of Impacted Pathways and Transcriptomic Markers as Potential Mediators of Pulmonary Fibrosis in Transgenic Mice Expressing Human IGFBP5 - Xinh-Xinh Nguyen (MDPI AG, 2021)
Pulmonary fibrosis is a serious disease characterized by extracellular matrix (ECM) component overproduction and remodeling. Insulin-like growth factor-binding protein 5 (IGFBP5) is a conserved member of the IGFBP family of proteins that is overexpressed in fibrotic tissues and promotes fibrosis. We used RNA sequencing (RNAseq) to identify differentially expressed genes (DEGs) between primary lung fibroblasts (pFBs) of homozygous (HOMO) transgenic mice expressing human IGFBP5 (hIGFBP5) and wild type mice (WT). The results of the differential expression analysis showed 2819 DEGs in hIGFBP5 pFBs. Functional enrichment analysis confirmed the pro-fibrotic character of IGFBP5 and revealed its impact on fundamental signaling pathways, including cytokine–cytokine receptor interaction, focal adhesion, AGE-RAGE signaling, calcium signaling, and neuroactive ligand-receptor interactions, to name a few. Noticeably, 7% of the DEGs in hIGFBP5-expressing pFBs are receptors and integrins. Furthermore, hub gene analysis revealed 12 hub genes including Fpr1, Bdkrb2, Mchr1, Nmur1, Cnr2, P2ry14, and Ptger3. Validation assays were performed to complement the RNAseq data. They confirmed significant differences in the levels of the corresponding proteins in cultured pFBs. Our study provides new insights into the molecular mechanism(s) of IGFBP5-associated pulmonary fibrosis through possible receptor interactions that drive fibrosis and tissue remodeling.